2008
DOI: 10.1016/j.taap.2007.12.026
|View full text |Cite
|
Sign up to set email alerts
|

The heavy metal cadmium induces valosin-containing protein (VCP)-mediated aggresome formation

Abstract: Cadmium (Cd 2+ ) is a heavy metal ion known to have a long biological half-life in humans. Accumulating evidence shows that exposure to Cd 2+ is associated with neurodegenerative diseases characterized by the retention of ubiquitinated and misfolded proteins in the lesions. Here, we report that Cd 2+ directly induces the formation of protein inclusion bodies in cells. The protein inclusion body is an aggresome, a major organelle for collecting ubiquitinated or misfolded proteins. Our results show that aggresom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Recently, Ubc was reported to be involved in arsenite-induced toxicity in mouse embryonic fibroblasts (MEFs) (Kim et al, 2015), suggesting that polyUb genes may be critical to the mechanism of metal(loid) toxicity. Cd causes the formation of protein inclusion bodies by promoting the accumulation of ubiquitinated proteins in aggresomes in HEK293 cells (Song et al, 2008), and it has been suggested that the Ub ligase FBXO6 reduces Cd toxicity by expediting degradation of misfolded proteins by the UPS in HEK293 cells (Du et al, 2014). The present study also suggests that accumulation of ubiquitinated proteins may increase Cd toxicity in HK-2 cells.…”
Section: A B C Dsupporting
confidence: 67%
“…Recently, Ubc was reported to be involved in arsenite-induced toxicity in mouse embryonic fibroblasts (MEFs) (Kim et al, 2015), suggesting that polyUb genes may be critical to the mechanism of metal(loid) toxicity. Cd causes the formation of protein inclusion bodies by promoting the accumulation of ubiquitinated proteins in aggresomes in HEK293 cells (Song et al, 2008), and it has been suggested that the Ub ligase FBXO6 reduces Cd toxicity by expediting degradation of misfolded proteins by the UPS in HEK293 cells (Du et al, 2014). The present study also suggests that accumulation of ubiquitinated proteins may increase Cd toxicity in HK-2 cells.…”
Section: A B C Dsupporting
confidence: 67%
“…Additionally, aggresome formation was reported in HEK293, CHO, NIH3T3, and mouse primary liver cells treated with 20 μM cadmium chloride (Song et al, 2008). To our knowledge, the induction of aggresome formation by sodium arsenite has not been reported in other systems.…”
Section: Discussionmentioning
confidence: 80%
“…Next, we investigated the mechanism of action by which CBZ alleviates aggresome formation by examining the expression, localization, and autophagy interaction of VCP (Figures 3 and 4A), a key mediator of both proteasomal and aggresomal protein processing pathways (47,48,59,(62)(63)(64)(65)(66). VCP is not only involved in translocating proteins to microtubule organizing centers (aggresomes) (23,67), but is also responsible for segregation and unfolding of ubiquitinated proteins from aggresome bodies for presentation to the protein degradation machinery (49,64 1 aggresome bodies to assist with autophagy-mediated protein degradation, potentially by inducing its segregase/ unfoldase activity to process and present aggregated proteins to autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we focused on evaluating whether this dose of CBZ modulates ubiquitination and protein aggregation via valosin-containing protein (VCP), as it is known to play a critical role in autophagy-mediated protein degradation (46)(47)(48)(49). We observed that neither ubiquitinated nor total VCP protein levels were affected by short-term autophagy induction (CBZ) in the presence or absence of lysosome inhibitor ( Figure 3A).…”
Section: Autophagy Induction Modulates Valosin-containing Protein Locmentioning
confidence: 99%